Application of Endurance Time method in evaluation of seismic performance of a typical sandwich panel building - Mohammad Yekrangnia (Numerical Methods in Civil Engineering)
This study deals with the seismic performance evaluation of a typical five-story sandwich panel building with load-bearing wall as the only lateral force-resisting structural elements. For this purpose, incremental dynamic analyses (IDA) were performed on the model making use of seven selected ground motions. As a substitute to IDA, the response of the model in terms of maximum plastic strain, base shear and the inter-story drift ratio of the first story were compared with those from Endurance Time (ET) analysis. The results show that ET can simulate the seismic response of the studies model with an acceptable accuracy. However, the discrepancy between the ET results and those of the real ground motions increases with by increasing the excitation intensity. In general, ET underpredicts the drift ratios in very intense excitations, whereas the error of base shear with respect to the real ground motions remains almost constant regardless of the ground motion intensity.